The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cb.1936
|View full text |Cite
|
Sign up to set email alerts
|

How trust leads to online purchase intention founded in perceived usefulness and peer communication

Abstract: This study seeks to understand the specific factors on social media that help drive the intention to purchase fashion‐related products, focusing on the central role of trust. The unique contribution of this research lies in its exploration of the interplay between perceived usefulness of the fashion brand's social media and peer communication on the fashion brand's social media in driving trust in the fashion brand's social media and, ultimately, purchase intention. Theoretically, we combine the technology acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
61
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 111 publications
11
61
2
5
Order By: Relevance
“…Peer communication and peer condition are positively related to fear of COVID-19. As we know, peer communication and peer condition as important factors of peer influence affect individuals’ affections and emotions, and previous studies have indicated that peer influence produces more negative than positive effects ( Bexkens et al, 2019 ; Harrigan et al, 2021 ; Youn & Shin, 2019 ). This study verifies the previous results and finds that both peer communication and peer condition about COVID-19 tend to produce negative effects, namely, fear of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Peer communication and peer condition are positively related to fear of COVID-19. As we know, peer communication and peer condition as important factors of peer influence affect individuals’ affections and emotions, and previous studies have indicated that peer influence produces more negative than positive effects ( Bexkens et al, 2019 ; Harrigan et al, 2021 ; Youn & Shin, 2019 ). This study verifies the previous results and finds that both peer communication and peer condition about COVID-19 tend to produce negative effects, namely, fear of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Peer communication and peer condition as important factors of peer influence impact individuals’ affections and behaviors ( Bexkens et al, 2019 ; Harrigan et al, 2021 ; Youn & Shin, 2019 ). Peer communication refers to obvious peer interactions among publics, which is regarded as an important component of public social media engagement ( Ai et al, 2016 ; Qin & Men, 2019 ).…”
Section: Theory Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, they need to be able to raise feelings of accessibility and a “warm personal relationship” [ 49 ] (p. 5). Additionally, the ability to establish and maintain a trusting relationship seems to be of crucial importance [ 51 ], which can enable and be enabled through interpersonal contacts [ 52 ]. Correspondingly, personal closeness (family, close friends) and trust in the counterparts’ competence in food matters (schools, teachers, doctors) play a key role in developing food preferences and choice [ 35 , 53 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%